Mechanical axial instability of segmental pedicle screw instrumentation for adolescent idiopathic scoliosis: a retrospective cohort study of tulip screw versus dual locking cup instrumentation - Aron Frantzén; Antti Saarinen; Eetu Suominen; Matti Ahonen; Ilkka Helenius (Acta Orthopaedica)
Background and purpose: The effects of axial instability in the rod–screw interface resulting in axial slippage between screws and rods are largely unknown. We aimed to assess the incidence of axial slip and loss of correction by comparing tulip screw versus dual locking cup in spinal instrumentations of patients treated with posterior spinal fusion for adolescent idiopathic scoliosis (AIS). We also aimed to assess whether axial slip would affect health-related quality of life. Methods: This study consists of 194 patients who underwent posterior spinal fusion for AIS during 2012–2022. All patients had a minimum of 2 years’ follow-up. There were 98 patients treated with segmental tulip pedicle screw instrumentation and 96 patients with segmental dual locking cup constructs. Axial slip was defined as ≥ 2 mm and was assessed by measuring the rod exceeding the last pedicle screw and the distance between the 2 lowest screws on the same rod. Loss of correction was assessed by comparing postoperative and 2-year radiographic measurements. Health-related quality of life was assessed using the SRS-24 questionnaire. Results: Axial slip occurred only between the lowest instrumented vertebra and the vertebra above it on the convex side of the deformity. At 2 years of follow-up, axial slippage of 2 mm or more was observed more often in the dual locking group, which was observed in 24 (25%) patients in the dual locking cup group and 11 (11%) patients in the tulip group (risk ratio [RR] 2.2, 95% confidence interval [CI] 1.2–4.4). Minimum of 10° loss of major curve correction was found in 1 (1%) patient in the tulip group and 9 (9%) patients in the dual locking group (RR 9.1, CI 1.2–100). Conclusion: Axial slip was significantly less frequent in the tulip group than in the dual locking cup group. This suggests that tulip screw instrumentation may offer superior mechanical stability in posterior spinal fusion for AIS. Axial slip was not associated with health-related quality of life outcomes.